Suburban schools as sites of inspection: Understanding Latinx youth's sense of belonging in a suburban high school. Issue 1 (2nd April 2020) - Rodriguez, Gabriel
ABSTRACT: Through a critical ethnographic approach, this study examines how Latinx youth made sense of race, space, and place at a predominantly white, well-resourced suburban high school outside of Chicago, Illinois. Employing spatial theory and borderland theory, I analyze the experiences of 19 Latinx youth to learn how they understood and navigated the racialized borders of their school and how that, in turn, shaped how they built a sense of belonging for themselves. The findings focus on how whiteness and white youth set the stage for how Latinx youth take up space and build community. Moreover, despite the constraints they endure, Latinx youth enact their agency in ways that can help schools reimagine how to create more inclusive student communities.